ANALYSIS OF THE MOTIVES AND LEVEL OF SATISFACTION OF USERS OF VIDIO.COM AS STREAMING MEDIA IN INDONESIA - Muhammad Alfinka Dwiana Putra Pamuji; Daru Purnomo; Seto Herwandito (International Journal of Social Science, 2023)
This research is entitled "Analysis of the Satisfaction Level of Vidio.com Users as Streaming Media in Indonesia" and has the purpose of measuring the level of satisfaction of Vidio.com users. In disruption era 4.0, which allows technology to develop rapidly resulting in all forms of change. For example, there is a transition from the usage of television to streaming media or Over-The-Top (OTT) such as Vidio.com. Vidio.com is an OTT service, that offers content delivery directly to consumers who are number 1 in Indonesia. This research uses descriptive quantitative research methods with the theory applied, which is Uses and Gratifications, measured by the motive of use and the motive of satisfaction which can be measured by the motive of need. With 400 respondents, the majority of age between 19-34 years old and domiciled in Jakarta, the research found that the motives of personal integration and social integration provided satisfaction to Vidio.com users. With GS < GO values, the results are 9.8100 < 9.8925 for personal integration and 9.6875 < 9.7850 for social integration. This indicates that Vidio.com has not been able to provide satisfaction to its users because three of the five existing motives have not been fulfilled.